2022
DOI: 10.3389/fimmu.2022.837262
|View full text |Cite
|
Sign up to set email alerts
|

IL25 Enhanced Colitis-Associated Tumorigenesis in Mice by Upregulating Transcription Factor GLI1

Abstract: Interleukin-25 (IL17E/IL25) plays a critical role in colitis and intestinal homeostasis. However, the expression and biological role of IL25 in colorectal cancer is not properly understood. In this study, we show that IL25 is mainly expressed by cancer stem cells in the colorectal cancer microenvironment. Genetic deletion of IL25 inhibited tumor formation and growth and prolonged survival in AOM/DSS-treated mice. IL25 stimulated cancer organoid and cancer cells sphere formation and prevented the tumor from che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Analysis of IL-25 expression in healthy colons and CRC showed comparable levels in one report (78), while a more recent study found IL-25 expression to be elevated in human CRC tumours compared to the adjacent normal gut (80). Similar to the homeostatic intestine and mirroring IL-25 expression during parasitic infection (30), DCLK1 + tuft cells were found to be the main source of IL-25 in tumours in mouse models of APCmutation-mediated CRC (Apc 1322T/+ ) (81) and azoxymethane (AOM)/dextran sodium sulphate (DSS)-mediated model of colitis associated cancer (CAC) (80), indicating that IL-25 expression by tuft cells is conserved across different subtypes of CRC. Recently, analysis of the publicly available gene expression databases found that high IL25 expression by CRC tumours was associated with reduced CRC patient disease-free survival (81).…”
Section: Il-25 In Crcsupporting
confidence: 59%
See 4 more Smart Citations
“…Analysis of IL-25 expression in healthy colons and CRC showed comparable levels in one report (78), while a more recent study found IL-25 expression to be elevated in human CRC tumours compared to the adjacent normal gut (80). Similar to the homeostatic intestine and mirroring IL-25 expression during parasitic infection (30), DCLK1 + tuft cells were found to be the main source of IL-25 in tumours in mouse models of APCmutation-mediated CRC (Apc 1322T/+ ) (81) and azoxymethane (AOM)/dextran sodium sulphate (DSS)-mediated model of colitis associated cancer (CAC) (80), indicating that IL-25 expression by tuft cells is conserved across different subtypes of CRC. Recently, analysis of the publicly available gene expression databases found that high IL25 expression by CRC tumours was associated with reduced CRC patient disease-free survival (81).…”
Section: Il-25 In Crcsupporting
confidence: 59%
“…Conversely, conflicting reports have shown that both IL-33 and IL-25 may either promote or inhibit CAC (Table 1) (80,82,90,92,96,97), and therefore caution should be taken when considering IL-25 or IL-33-based therapy in this cohort. Another strategy would be to target IL-25 or IL-33 during early stages of IBD, to delay or prevent progression into intestinal cancer while resolving the colitis.…”
Section: Future Perspectives -Il-25 and Il-33 In Cancer Immunotherapymentioning
confidence: 87%
See 3 more Smart Citations